Question
upstudy study bank question image url

Rewrite the expressions that follow as the sine or cosine of a single angle and evaluate where possible without a calculator. \( 2.1 \sin 68^{\circ} \cos 22^{\circ}+\cos 68^{\circ} \sin 22^{\circ} \) \( 2.2 \cos 28^{\circ} \cos 2^{\circ}-\sin 28^{\circ} \sin 2^{\circ} \) \( 2.3 \cos 108^{\circ} \cos 188^{\circ}+\sin 252^{\circ} \sin 172^{\circ} \) \( 2.4 \sin 70^{\circ} \cos 10^{\circ}-\cos 80^{\circ} \cos 70^{\circ} \) \( -\sin 4 x \sin 3 x+\cos 4 x \cos 3 x \) \( 2.6 \sin \left(90^{\circ}-x\right) \cos x+\cos \left(90^{\circ}+x\right) \sin x \)

Ask by Lyons Salinas. in South Africa
Feb 26,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

1. \( 2.1 = 2 \) 2. \( 2.2 = \frac{\sqrt{3}}{2} \) 3. \( 2.3 = \sin(10^{\circ}) \) 4. \( 2.4 = \frac{\sqrt{3}}{2} \) 5. \( 2.5 = \cos(x) \) 6. \( 2.6 = \cos(2x) \)

Solution

To rewrite the given expressions as the sine or cosine of a single angle, we can use the angle addition and subtraction formulas. Let's go through each expression step by step. ### Expression 2.1 \[ 2.1 \quad 2 \sin 68^{\circ} \cos 22^{\circ} + \cos 68^{\circ} \sin 22^{\circ} \] Using the angle addition formula for sine: \[ \sin(a + b) = \sin a \cos b + \cos a \sin b \] we can rewrite the expression as: \[ 2 \sin(68^{\circ} + 22^{\circ}) = 2 \sin(90^{\circ}) = 2 \] ### Expression 2.2 \[ 2.2 \quad \cos 28^{\circ} \cos 2^{\circ} - \sin 28^{\circ} \sin 2^{\circ} \] Using the angle subtraction formula for cosine: \[ \cos(a + b) = \cos a \cos b - \sin a \sin b \] we can rewrite the expression as: \[ \cos(28^{\circ} + 2^{\circ}) = \cos(30^{\circ}) = \frac{\sqrt{3}}{2} \] ### Expression 2.3 \[ 2.3 \quad \cos 108^{\circ} \cos 188^{\circ} + \sin 252^{\circ} \sin 172^{\circ} \] Using the angle addition formula for cosine: \[ \cos(a - b) = \cos a \cos b + \sin a \sin b \] we can rewrite the expression as: \[ \cos(108^{\circ} - 188^{\circ}) = \cos(-80^{\circ}) = \cos(80^{\circ}) = \sin(10^{\circ}) \] ### Expression 2.4 \[ 2.4 \quad \sin 70^{\circ} \cos 10^{\circ} - \cos 80^{\circ} \cos 70^{\circ} \] Using the sine subtraction formula: \[ \sin(a) \cos(b) - \cos(a) \cos(b) = \sin(a - b) \] we can rewrite the expression as: \[ \sin(70^{\circ} - 10^{\circ}) = \sin(60^{\circ}) = \frac{\sqrt{3}}{2} \] ### Expression 2.5 \[ 2.5 \quad -\sin 4x \sin 3x + \cos 4x \cos 3x \] Using the cosine subtraction formula: \[ \cos(a - b) = \cos a \cos b + \sin a \sin b \] we can rewrite the expression as: \[ \cos(4x - 3x) = \cos(x) \] ### Expression 2.6 \[ 2.6 \quad \sin(90^{\circ} - x) \cos x + \cos(90^{\circ} + x) \sin x \] Using the sine and cosine identities: \[ \sin(90^{\circ} - x) = \cos x \quad \text{and} \quad \cos(90^{\circ} + x) = -\sin x \] we can rewrite the expression as: \[ \cos x \cos x - \sin x \sin x = \cos^2 x - \sin^2 x = \cos(2x) \] ### Summary of Results 1. \( 2.1 = 2 \) 2. \( 2.2 = \frac{\sqrt{3}}{2} \) 3. \( 2.3 = \sin(10^{\circ}) \) 4. \( 2.4 = \frac{\sqrt{3}}{2} \) 5. \( 2.5 = \cos(x) \) 6. \( 2.6 = \cos(2x) \)

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

Sure! Here are the rewritten expressions: **2.1** We can use the sine addition formula: \( 2.1 \sin 68^{\circ} \cos 22^{\circ}+\cos 68^{\circ} \sin 22^{\circ} = \sin(68^{\circ} + 22^{\circ}) = \sin 90^{\circ} = 1 \) **2.2** We utilize the cosine subtraction formula: \( 2.2 \cos 28^{\circ} \cos 2^{\circ}-\sin 28^{\circ} \sin 2^{\circ} = \cos(28^{\circ} + 2^{\circ}) = \cos 30^{\circ} = \frac{\sqrt{3}}{2} \) **2.3** For this expression, we can use the cosine addition formula: \( 2.3 \cos 108^{\circ} \cos 188^{\circ}+\sin 252^{\circ} \sin 172^{\circ} = \cos(108^{\circ} - 188^{\circ}) = \cos(-80^{\circ}) = \cos 80^{\circ} = \sin 10^{\circ} \) **2.4** Now we apply the sine and cosine subtraction formulas: \( 2.4 \sin 70^{\circ} \cos 10^{\circ}-\cos 80^{\circ} \cos 70^{\circ} = \sin(70^{\circ} - 10^{\circ}) = \sin 60^{\circ} = \frac{\sqrt{3}}{2} \) **2.5** This simplifies using the cosine addition formula: \( -\sin 4 x \sin 3 x+\cos 4 x \cos 3 x = \cos(4x - 3x) = \cos x \) **2.6** We can transform using known identities: \( 2.6 \sin \left(90^{\circ}-x\right) \cos x+\cos \left(90^{\circ}+x\right) \sin x = \cos x \cos x - (-\sin x \sin x) = \cos^2 x + \sin^2 x = 1 \)

Related Questions

Latest Trigonometry Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy